Market Insight into Contemporary Practices for Green Supply Chain of a Logistics Company in Pakistan - Abdullah, Muhammad Khan (2024)
According to Patrick Penfield of the Whiteman School of Management, green supply chain management (GSCM) is utilizing beneficial inputs and converting them into outputs that may be recycled and recovered at the end of their useful lives. This study examines the GSCM procedures that DHL Pakistan has put in place, with an emphasis on proactive and reactive tactics and how they affect the logistics industry's economic, intangible, and environmental performance. The moderating role of the "Market" in this study is essential because it keeps the research useful and relevant by shedding light on industry changes, market dynamics, and environmental sustainability initiatives. This study's main focus is on the logistics sector's (DHL in particular) shift from traditional supply chain management to global supply chain management (GSCM). According to the study, improving commercial, economic, and environmental performance levels are only a few of the performance benefits that may be attained by efficiently coordinating internal and external GSCM processes. A thorough evaluation of all notable journals, books, research papers, and periodicals published between 2016 and 2020 was part of the research process. Using information from these sources, a quantitative study was performed with an emphasis on important GSCM projects carried out by different companies, as well as well-known writers. The goal of the data analysis was to pinpoint important suggestions and advantages of GSCM methods. Key findings suggest that performance advantages can be optimized by implementing GSCM approaches in a particular order. The results emphasize how crucial market factors are to improving GSCM techniques' efficacy in Pakistan's logistics industry. The study's result emphasizes the necessity of integrated GSCM procedures in order to attain long-term performance gains. The knowledge gathered from this study advances our comprehension of how logistics firms such as DHL may successfully make the shift to green supply chain management.